Earlier vegetation green-up is intensifying hydrological drought in the Tianshan Mountain basins - Lilin Zheng; Ruishan Chen; Jianhua Xu; Yinshuai Li; Nan Jia; Xiaona Guo (Journal of Hydrology: Regional Studies)
Study region: Two inland basins in the Tianshan Mountains: the Huangshui Basin (HSB) and the Kashi Basin (KSB). Study focus: Earlier green-up driven by climate warming can profoundly alter hydrological processes. However, the isolated impact of phenological changes on hydrological dynamics, independent of climatic factors, remains largely unexplored. To address this gap, we quantified the contributions of earlier green-up to evapotranspiration (ET) and basin streamflow by developing a framework that integrates an NDPI-based phenology model with the RHESSys eco-hydrological model. New hydrological insights for the region: Between 2001 and 2020, the start of the growing season (SOS) advanced at rates of 1.02 days/year in HSB and 0.97 days/year in KSB, while changes in the end of the growing season were minimal (0.17 and − 0.12 days/year, respectively). In HSB, each one-day advancement in green-up increased ET by 2.22 mm and reduced streamflow discharge by 2.35 million m³. In contrast, in KSB, a one-day advancement in green-up resulted in a more significant increase in ET (11.22 mm) and a more substantial reduction in streamflow discharge (58.24 million m³). KSB's westward-facing topography facilitates the inflow of warm, humid Atlantic air, contributing to a more humid climate, higher vegetation cover, and an earlier SOS compared to HSB. These findings highlight the importance of incorporating phenological dynamics into eco-hydrological assessments to develop effective climate adaptation strategies for inland mountain basins.